National Election Study, 1948 ([Verlag nicht ermittelbar], 1984)
This study contains data on the attitudes and opinions of voters toward the political parties and the political process in the United States in 1948. The study was conducted in May 1948, before the political party conventions. Respondents were probed about their feelings toward the Republican, Democratic, and the Wallace Third parties, and taxes. They were also questioned about party identification, party differences, the most important problems facing the government and their own families, the possibility of the United States' involvement in another war in the next five years, the 1944 vote, and their voting intentions. In addition, respondents were asked to evaluate Truman's general performance as president, and to respond to questions gauging their satisfaction or dissatisfaction with Truman's policy toward Russia, labor unions, minority groups, and Palestine. Their opinions were also sought about who to blame for the high cost of living and the trouble between labor and management. Demographic items specify age, sex, race, nationality, education, occupation, religion, political party affiliation, labor union membership, ideological orientation, and veteran status.